(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In wireless ad-hoc networks, there areseveral characteristics different with wired networks. Thedifferences are changing of network topology, limitedresources like bandwidth and energy and so on. In thesedays as the bandwidth issue becomes more important, it isrequired to research about the efficient resource allocationmethods optimized in wireless network ks. In the paper,we improve LAR (Location-Aided Routing) which is oneof the most famous location based routing methods. Thiskind of technique uses information about the location ofmobile node through GPS technique. Our new protocolconsiders both areas of routing and bandwidth. At first,propose a more efficient routing method which improvesthe quality of services .Secondly, a bandwidth awaremethod is proposed to select proper transmissionbandwidth node by using a threshold value of bandwidth